Ultrasonography-guided removal of plant-based foreign bodies from the lacrimal sac in four dogs - Giovanni Barsotti; Tommaso Mannucci; Simonetta Citi (BMC Veterinary Research, 2019)
Abstract Background Dacryocystitis is an inflammation of the lacrimal drainage system. One of the most common causes of dacryocystitis in dogs is due to plant-based foreign bodies typically located in the lacrimal sac. The aim of this case series was to describe an ultrasonography-guided technique for dogs with plant-based foreign bodies in the lacrimal sac, as both a diagnostic and therapeutic tool. Case presentation Four dogs with clinically suspected plant-based foreign body in the lacrimal sac (with a total of five eyes affected) were evaluated by ultrasound with a multifrequency (8–14 MHz) linear probe. Under general anesthesia, the foreign body was removed using Hartmann alligator forceps inserted thorough the upper puncta. Ultrasound was used to guide the forceps in grasping the foreign body. Ultrasound was positive in four out of five lacrimal sac diseases. All identified foreign bodies were successfully removed by the ultrasonography-guided technique. Conclusions The results show that ultrasound is a fast, non-invasive, and inexpensive method for the assessment of dacryocystitis due to foreign bodies in dogs. Ultrasound is also useful not only for identification, but also in the non-invasive removal of the foreign body from the lacrimal sac. To the best of authors’ knowledge, this is the first study to describe the sonographic approach to the palpebral medial cantus as an initial diagnostic step in canine dacriocystitis.